Which private investors are willing to pay for sustainable investments? Empirical evidence from stated choice experiments - Gutsche, Gunnar; Ziegler, Andreas (Journal of Banking & Finance, 2019)
Based on data from a representative survey among German private financial decision makers that comprised two stated choice experiments for fixed-interest investment products and equity funds, this paper empirically examines whether and which investors are willing to pay for sustainable investments. In fact, our econometric analyses with mixed and latent class logit models reveal strong stated preferences and a considerable willingness to pay (WTP) for sustainable investment products. Furthermore, our mixed logit model analysis implies that the mean WTP for certified sustainable investment products is strongly higher than the mean WTP for the uncertified counterparts. In addition, our estimation results suggest that investors with high feelings of warm glow from sustainable investments, an affinity to left-wing parties, and a strong environmental awareness have a clearly higher mean willingness to sacrifice returns for sustainable investment products than their counterparts. While risk perceptions seem to be additionally relevant for certified sustainable equity funds, they obviously play a negligible role for less risky sustainable fixed-interest investment products.